Rapid Skill-Builder Emotional Intelligence - Fenman (United Kingdom World Center for Organisational Development, 2007)
Your success depends on more than just your knowledge, skills, or what is often termed "intelligence". In both personal and professional life, emotional intelligence, or your ability to connect appropriately with other people and the world around you, is crucial to sustained success. Emotional intelligence can be described as the ability to: Perceive or sense emotion Use emotions to assist thought Understand emotions Manage emotions Every person has emotional intelligence (also known as EI or EQ) to some degree. However, how each person actually applies his or her EQ can vary considerably. This Skill Builder provides an introduction to the subject of emotional intelligence and proposes a four quadrant style model which can help you to learn how to apply feelings appropriately across a range of situations and experiences in order to become more emotionally "intelligent"
Includes 3
Keywords: Emotional Intelligence